Examining the gas-phase homodimers of 3, 3, 3-trifluoro-1, 2-epoxypropane using quantum chemistry and microwave spectroscopy. Issue 46 (21st November 2022) - Marshall, Mark D.; Leung, Helen O.; Domingos, Sérgio R.; Krin, Anna; Schnell, Melanie; Seifert, Nathan A.; Xu, Yunjie; Jäger, Wolfgang
Abstract : Quantum chemistry and rotational spectroscopy work hand-in-hand in the characterization of a potential chiral tag. Abstract : Gas phase homodimers of 3, 3, 3-trifluoro-1, 2-epoxypropane (TFO), a molecule which has shown promise as an effective chiral tag for determining the absolute stereochemistry and the enantiomeric composition of chiral analytes, are explored using a variety of quantum chemistry models and rotational spectroscopy. The potential surface governing the interaction of the two molecules is rapidly explored using the artificial bee colony algorithm for homodimer candidates that are subsequently optimized by quantum chemistry methods. Although all model chemistries employed agree that the lowest energy form of the heterochiral homodimer of TFO ( RS or SR ) is lower in energy than that of the homochiral dimer ( RR or SS ), the energy spacings among the lower energy isomers of each and indeed the absolute energy ordering of the isomers of each are very model dependent. The experimental results suggest that the B3LYP-D3BJ/def2-TZVP model chemistry is the most reliable and provides excellent estimates of spectroscopic constants. In accord with theoretical predictions the non-polar lowest energy form of the heterochiral homodimer is not observed, while two isomers of the homochiral dimer are observed and spectroscopically characterized. Observation and assignment of the spectra for all three unique singly-substituted 13 C isotopologues, in addition to that of the most abundant isotopologue for the lowest energy isomer of the homochiral homodimer of TFO, provide structural information that compares very favorably with theoretical predictions, most notably that the presence of three fluorine atoms on the trifluoromethyl group removes their direct participation in the intermolecular interactions, which instead comprise two equivalent pairs of CH⋯O hydrogen bonds between the two epoxide rings augmented by favorable dispersion interactions between the rings themselves.